Penguatan Manajemen Bisnis berbasih Syariah pada Kelompok Perempuan Aisyiyah Ranting Kenongo Sidoarjo - Menur Kusumaningtyas; Johni Harius Putranto; Fitri Nur Latifah (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This community service program aims to strengthen the capacity of women entrepreneurs in implementing sharia-based business management. The participants consisted of 20 women from Aisyiyah Kenongo Branch, Sidoarjo, who are engaged in micro-scale businesses. Although the participants had basic knowledge of sharia business principles, their implementation in daily business practices was still limited, particularly in terms of contract (akad) application, financial record-keeping, and business development strategies. The program employed a participatory approach through socialization, training, and mentoring activities. The materials covered fundamental principles of sharia business, transaction contracts, simple financial management, and the utilization of digital technology to support business activities. The results indicate a significant improvement in participants’ understanding of sharia-based business practices, as well as positive changes in their business behavior, including increased transparency in transactions and the adoption of basic financial recording systems. Furthermore, the program enhanced participants’ confidence and encouraged collaboration among members. Therefore, this community service initiative contributes to the sustainable empowerment of women’s economic activities based on sharia values and adaptive digital practices.